2022
DOI: 10.3389/fmed.2021.803837
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Molecular Epidemiology of Escherichia coli From Bloodstream Infection in Shanghai, China, 2016–2019

Abstract: Background: Bloodstream infections are recognized as important nosocomial infections. Escherichia coli (E. coli) is the most prevalent Gram-negative bacillary pathogen causing bloodstream infections (BSIs). This retrospective study investigated drug susceptibility and molecular epidemiology of E. coli isolated from patients with BSI in Shanghai, China.Methods: We collected E. coli isolated from the blood cultures of patients with BSI between January 2016 and December 2019. We randomly selected 20 strains each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Comparing with our finding Kahlmeter, (2003) found that E. coli isolates from human urinary tract infections were highly susceptible to Nitrofurantoin, Fosfomycin, and Mecillinam, while susceptibility to Trimethoprim/Sulfamethoxazole, Ciprofloxacin, and Gentamicin varied. Consistence with our finding, other studies on E. coli by Xiao et al (2022). Paudel et al (2023) showed high susceptibility to Imipenem and Amikacin, but lower susceptibility to Ampicillin, and Levofloxacin.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing with our finding Kahlmeter, (2003) found that E. coli isolates from human urinary tract infections were highly susceptible to Nitrofurantoin, Fosfomycin, and Mecillinam, while susceptibility to Trimethoprim/Sulfamethoxazole, Ciprofloxacin, and Gentamicin varied. Consistence with our finding, other studies on E. coli by Xiao et al (2022). Paudel et al (2023) showed high susceptibility to Imipenem and Amikacin, but lower susceptibility to Ampicillin, and Levofloxacin.…”
Section: Discussionsupporting
confidence: 91%
“…This work investigated the genomic characteristics of ESBL- E. coli isolated from chicken farms and human medical clinics of Sichuan Province and Yunnan Province, China. The isolation rate of ESBL- E. coli in Sichuan Province was 48% (48/100), whereas that in Yunnan Province was 45.35% (156/344); both were slightly lower than the 58.8% rate in Shanghai ( 36 ). We found that the prevalence rate of chicken farm-derived ESBL- E. coli was 34.34% (204/594), which was significantly lower than the 78.6% reported by Liu et al ( 37 ).…”
Section: Discussionmentioning
confidence: 77%
“…In recent times, the ST131 clone has emerged as the foremost and highly potent multi-drug resistant (MDR) clone on a global scale, serving as a major etiological factor for community-acquired urinary and bacteremic infections. 20 , 21 ST1193 clone follows closely due to its prevalent overuse of Fluoroquinolone (FQ) and third-generation cephalosporin. 22 Birgy et al 23 revealed that ST1193 constituted one of the most prevalent clones during the final study phase, among 218 ESBL-producing E. coli infections that resulted in febrile urinary tract infections in children between 2014 and 2017.…”
Section: Discussionmentioning
confidence: 99%